Enhancing sustainable performance through innovation: the role of AI and digitalisation in maritime companies - Tok, Pei Qi (Nanyang Technological University, 2023)
This study aims to investigate how Artificial Intelligence (AI) and digitalisation drive sustainable performance of maritime companies. A theoretical model was proposed to investigate the technologies affecting the triple bottom line. Organisational ambidexterity was hypothesised to be a key link between technologies and sustainable performance. An online survey was conducted and 124 valid responses were collected. Thereafter, the data were analysed using structural equation modelling. Results revealed that digital culture and Internet of Things influence exploitative innovation. Digital leadership, Internet of Things and big data analytics influence explorative innovation. Digital leadership, exploitative innovation and explorative innovation influence sustainable performance, carrying satisfactory explanatory power (R2 = 34%). Total effect analysis has shown that digital leadership is the main predictor of sustainable performance and focusing on developing digital leadership within the organisation is an important step in enhancing the triple bottom line. Overall, this study enriches current studies on the effect of technologies on sustainable performance, providing insights on theoretical implications through the introduction of organisational ambidexterity as an intermediate factor. Awareness is brought to the effects of intangible technologies, which are usually implicitly communicated in an organisation. It also provides strategy implications for maritime companies to consider in order to drive sustainable performance.